2009
DOI: 10.1107/s0108768108041876
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic proton disorder and the II–I structural phase transition in (NH4)3H(SO4)2

Abstract: X-ray powder diffraction, differential scanning calorimetry (DSC)/thermogravimetry (TG) and single-crystal neutron diffraction methods were used to investigate triammonium hydrogen disulfate (NH(4))(3)H(SO(4))(2) (TAHS) in the temperature range between 293 and 493 K. The temperature-dependent X-ray powder diffraction measurements show a clear hysteresis of the I <-->II phase transition of TAHS with transition temperatures of T(up) = 412.9 (1) K on heating and of T(down) = 402.6 (1) K on cooling. From the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…1, when these atoms are excluded from calculations. The H1 splitting consistent with our split model from room-temperature results (Sohn et al, 2009) moved the H1 proton from the 9e Wyckoff position with a site occupation factor of 1/3 to the 18h Wyckoff position with a site occupation factor of 1/6 in TAHS-I. The disorder of the H1 atom has already been postulated by Friese et al (2002), although no displacement from the ideal position could be shown by their X-ray data.…”
Section: Crystal Structure Of Tahs-i: Split-atom Modelsupporting
confidence: 81%
See 2 more Smart Citations
“…1, when these atoms are excluded from calculations. The H1 splitting consistent with our split model from room-temperature results (Sohn et al, 2009) moved the H1 proton from the 9e Wyckoff position with a site occupation factor of 1/3 to the 18h Wyckoff position with a site occupation factor of 1/6 in TAHS-I. The disorder of the H1 atom has already been postulated by Friese et al (2002), although no displacement from the ideal position could be shown by their X-ray data.…”
Section: Crystal Structure Of Tahs-i: Split-atom Modelsupporting
confidence: 81%
“…This observation also supports proton conduction in the (001) plane as assumed by Merinov et al (2000). Our previous investigation of TAHS-II by single-crystal neutron diffraction at room temperature showed a disordering of the H atom of (SO 4 )H(SO 4 ) around the inversion centre in the middle of the dimer (Sohn et al, 2009). In the structure analysis this disordered H atom was refined using a split-atom model.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The ADPs of the ammonium groups on general positions shrink distinctly with decreasing temperature, while there is little change in ADPs of the ammonium groups on special positions. In contrast to the competing N-HÁ Á ÁO hydrogen bonds with a bifurcation at room temperature (Sohn et al, 2009), shorter, hence stronger single bonds are mainly formed in this phase. This results in a preferred orientation of these ammonium groups, suggesting a freezing of their reorientational motion.…”
Section: Figurementioning
confidence: 84%
“…Detailed crystal structure analyses have been carried out by single-crystal X-ray diffraction over a wide temperature range of 120-420 K (Swain & Row, 2007;Dominiak et al, 2003;Friese et al, 2002) and by single-crystal neutron diffraction in the high-and room-temperature phases, I and II, respectively (Sohn et al, 2009(Sohn et al, , 2011. The strong hydrogen bonds between two SO 2À 4 ions build a two-dimensional network in the hightemperature phase I, which allows proton diffusion between partly occupied proton sites and leads to superprotonic conductivity.…”
Section: Introductionmentioning
confidence: 99%